Social structures and their impacts on the field of university education in music at federal universities in the Brazil (Research, Society and Development, 2021)
This is a theoretical article of a sociological and educational nature that aims to analyze and debate the historical and social aspects that permeate the use of Specific Skill Tests in Music Degree Courses at Brazilian federal universities. From the structuralist and reproductive perspectives of Bourdieu (1996, 2007, 2009) and Pereira's concept of conservatorial habitus (2012), we propose a brief debate on the relations of domination in social structures and their impacts in the field of higher education in federal universities. It was concluded, from the perspectives of Bourdieu (1996, 2007, 2009), Pereira (2012) and Thiry-Cherques (2006), that the Specific Skill Tests are used as reproductive tools of a dominant social system that restricts, consciously or unconsciously, access to undergraduate music courses for the least favored classes. There is a need for a more in-depth debate on this topic in order to create a favorable environment for the democratization of access to higher musical knowledge, through free and quality teaching at Brazilian universities.